2015
DOI: 10.1016/j.socscimed.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Everyday drug diversions: A qualitative study of the illicit exchange and non-medical use of prescription stimulants on a university campus

Abstract: This article investigates everyday experiences and practises that are associated with processes of pharmaceuticalization and with practices of ‘drug diversion’—that is, the illicit exchange and non-medical use of prescription drugs. It reports results from a qualitative study that was designed to examine the everyday dimensions of non-medical prescription stimulant use among students on an American university campus, which involved 38 semi-structured interviews with individuals who used prescription stimulants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 40 publications
8
53
0
4
Order By: Relevance
“…These findings were similar to previous studies, which have found college students obtain prescription drugs from parents and peers [20,22]. Other research has found that black market sources are a frequently used avenue to obtain drugs [21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings were similar to previous studies, which have found college students obtain prescription drugs from parents and peers [20,22]. Other research has found that black market sources are a frequently used avenue to obtain drugs [21].…”
Section: Discussionsupporting
confidence: 92%
“…Minority students revealed several sources for obtaining prescription drugs including friends and the use of previously prescribed drugs (i.e., "leftover") that were saved for other purposes. The use of qualitative methods in this study provided an in-depth exploration of NMUPD among minority students; a population that is underrepresented in many larger studies [4,20,25]. The ideas for improving existing prevention and educational messages on college campuses that have the potential to improve knowledge and health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a revised coping model by Cooper et al (2008), we found that dysfunctional coping was related to CE use; however, this is unlikely to be the only factor related to students' enhancement practices. Previous studies have emphasized illicit drug use McCabe et al 2005;Schelle et al 2015); availability and association to other CE users (Desantis et al 2010;Vrecko 2015); and attitudes (Partridge et al 2012) as important drivers. It will therefore be important for future research to both replicate our main finding and to further explore the relationship between coping styles and the range of other factors known to impact CE use.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the originality of the subject and the implicit conflict between practices of rational use of medicines and the effects of pharmaceuticalization, there were only three articles found, two under the combination "pharmaceuticalization" OR "pharmaceuticalisation" AND "rational use of medicines" in the Virtual Health Library (BVS) 4 and Scielo 17 and another one under "pharmaceuticalization" OR "pharmaceuticalisation" AND "methylphenidate" on PubMed-Medline and Scopus 18 . There was a new attempt made under the same bases, using the terms "pharmaceuticalization" OR "pharmaceuticalisation" AND "cognitive enhancement" which also resulted in one article 19 .…”
Section: Methodsmentioning
confidence: 99%